Toxin–Antitoxin Systems in Bacillus subtilis - Brantl, Sabine (Toxins (Basel), 2019)
Toxin–antitoxin (TA) systems were originally discovered as plasmid maintenance systems in a multitude of free-living bacteria, but were afterwards found to also be widespread in bacterial chromosomes. TA loci comprise two genes, one coding for a stable toxin whose overexpression kills the cell or causes growth stasis, and the other coding for an unstable antitoxin that counteracts toxin action. Of the currently known six types of TA systems, in Bacillus subtilis, so far only type I and type II TA systems were found, all encoded on the chromosome. Here, we review our present knowledge of these systems, the mechanisms of antitoxin and toxin action, and the regulation of their expression, and we discuss their evolution and possible physiological role.